6x*6+3x*3=5x-2+2x*2

Simple and best practice solution for 6x*6+3x*3=5x-2+2x*2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x*6+3x*3=5x-2+2x*2 equation:


Simplifying
6x * 6 + 3x * 3 = 5x + -2 + 2x * 2

Reorder the terms for easier multiplication:
6 * 6x + 3x * 3 = 5x + -2 + 2x * 2

Multiply 6 * 6
36x + 3x * 3 = 5x + -2 + 2x * 2

Reorder the terms for easier multiplication:
36x + 3 * 3x = 5x + -2 + 2x * 2

Multiply 3 * 3
36x + 9x = 5x + -2 + 2x * 2

Combine like terms: 36x + 9x = 45x
45x = 5x + -2 + 2x * 2

Reorder the terms for easier multiplication:
45x = 5x + -2 + 2 * 2x

Multiply 2 * 2
45x = 5x + -2 + 4x

Reorder the terms:
45x = -2 + 5x + 4x

Combine like terms: 5x + 4x = 9x
45x = -2 + 9x

Solving
45x = -2 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
45x + -9x = -2 + 9x + -9x

Combine like terms: 45x + -9x = 36x
36x = -2 + 9x + -9x

Combine like terms: 9x + -9x = 0
36x = -2 + 0
36x = -2

Divide each side by '36'.
x = -0.05555555556

Simplifying
x = -0.05555555556

See similar equations:

| 7t-11t=16 | | 3x+4+2x+1=4+x | | 7-2+1-2x-5+3x=11-x | | -6(x+5)=66 | | 90=-6+8(p+4) | | (5n^2-n+6)+(8n^2-11)=0 | | 6+3=8x+4 | | -36+y=-2 | | -6(6x+8)=-36+48 | | 14y=350 | | 12x+13=115 | | 15y/12y^5 | | 0.3x-1=0.32 | | 5x*3-8+2x-4=2+3x*6 | | 120/10=-3y | | -12=-2.5x-3 | | 4-x+8=6 | | 2x+2x+3=-7 | | 0.5x+0.16=0.75 | | 6k^2-53k-9=0 | | 4x*6=8x-1 | | 4(x+9)=-24 | | 0.5x+6=0.75 | | -30=9/-5 | | 2-2n=3n+10 | | 4d-3=d+42 | | 5(N+1)=-2n+4(n-4) | | X-7+20=7x-10 | | -2/5÷-2/3 | | (3z+7)(3z+7)= | | 3x=.5(5x+12) | | y+5=-5x |

Equations solver categories